Volume 1: Processing 2016
DOI: 10.1115/msec2016-8562
|View full text |Cite
|
Sign up to set email alerts
|

Laser Sintered Graphene Reinforced Titanium Matrix Nanocomposites

Abstract: Graphene reinforced titanium (Ti-Gr) nanocomposites have been prepared on AISI 4140 base plate by laser sintering process. The dispersion and survival of graphene in the Ti matrix after laser treatment were discussed. Through laser sintering, graphene sheets were dispersed uniformly into Ti matrix to form Ti-Gr nanocomposites. Microstructures and components of the nanocomposites were studied using scanning electron microscopy (SEM), X-ray diffraction (XRD), energy dispersive spectrometer (EDS) and Raman spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Researchers revealed that graphene, uniformly distributed in the titanium matrix, still exists in the titanium matrix/multilayer graphene nanofiller composites prepared by SPS, despite the reactions between nano-carbon and titanium that occur during high-temperature sintering [ 21 ]. This indicated that it is possible that only the nano-carbon at the ends or defects react with titanium due to the presence of the vacuum environment and surface modification of nano-carbon, and the amount of nano-carbon that has reacted with titanium is very small [ 20 ]. Moreover, it was seen from Figure 7 and Figure 8 that C element is almost present in both the matrix phases and calcium-containing reactants, which indicates that the nano-carbon may be coated by matrix phases and calcium-containing reactants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers revealed that graphene, uniformly distributed in the titanium matrix, still exists in the titanium matrix/multilayer graphene nanofiller composites prepared by SPS, despite the reactions between nano-carbon and titanium that occur during high-temperature sintering [ 21 ]. This indicated that it is possible that only the nano-carbon at the ends or defects react with titanium due to the presence of the vacuum environment and surface modification of nano-carbon, and the amount of nano-carbon that has reacted with titanium is very small [ 20 ]. Moreover, it was seen from Figure 7 and Figure 8 that C element is almost present in both the matrix phases and calcium-containing reactants, which indicates that the nano-carbon may be coated by matrix phases and calcium-containing reactants.…”
Section: Resultsmentioning
confidence: 99%
“…The C element was also detected elsewhere in the samples, but no significant presence of nano-carbon was observed, which was because that the nano-carbon is coated with other phases. Moreover, the existence of nano-carbon was found on the surface of the Ti or HA composites in the many literatures [ 20 , 21 , 22 ]. Due to incomplete sintering, there were still some large agglomerated particles in the composite, as indicated by spot H in Figure 11 f. In addition, a large amount of granular particles (C, D) were present on the fracture surface, and mainly contained Ti, Nb, C, O, Ca, P, etc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, nano-carbon materials can enhance mechanical properties [32,75,76,77]. Hu et al revealed that Vickers hardness of Titanium-graphene composites initially increases with increasing of graphene content [71], as graphene itself has excellent mechanical properties that can carry loads and block dislocation movements in the composites. When the content of graphene was high, Vickers hardness of Titanium-graphene composites decreased [71], as graphene is a kind of 2D material, and its binding force with the matrix is weak.…”
Section: Strengthening and Toughening Mechanisms Of Titanium Alloymentioning
confidence: 99%